A thermosensitive poly(organophosphazene) hydrogel for injectable tissue-engineering applications - Yoon, Ji-Yeon; Park, Keun-Hong; Song, Soo-Chang (VSP BV, 2007)
A poly(organophosphazene) hydrogel has been synthesized which exhibits thermoreversible sol-gel transition behavior against temperature. Viscometric measurements indicated that a thermosensitive hydrogel exhibiting excellent strength could be formed at body temperature from the polymer solutions, at concentrations of 10 wt%. In this study, we have conducted an evaluation of this poly(organophosphazene) hydrogel with regard to its efficacy and suitability as an injectable tissueengineering matrix within an in vivo system. A 10 wt% solution of poly(organophosphazene) containing MC3T3-E1 mouse preosteoblasts and collagen was injected subcutaneously into nude mice, thereby forming an in situ gelation-injected site. In order to determine the optimal conditions for subcutaneous injection, various cell numbers and collagen concentrations were tested in this nude mouse model. Cellular proliferation was found to depend on the collagen concentration employed (0.001-0.1 wt%), as well as the number of cells ((2-10) x 10(5)). Cellular proliferation increased gradually after injection into nude mouse (1, 3, 5 and 7 days) at the given collagen concentration (0.01 wt%). The proliferative characteristics of MC3T3-E1 cells were shown to be enhanced dramatically in the poly(organophosphazene)-based collagen containing construct when injected into the model nude mice, whereas no increases in proliferation were observed in the only poly(organophosphazene) gel lacking collagen.
Keywords: CELL-ADHESION; IN-SITU; DELIVERY-SYSTEMS; DRUG-DELIVERY; SCAFFOLDS; GROWTH; RGD; PEPTIDES; POLYPHOSPHAZENES; PROLIFERATION